2007
DOI: 10.1080/10508610701402259
|View full text |Cite
|
Sign up to set email alerts
|

Religiousness and Depressive Symptoms in Five Ethnic Adolescent Groups

Abstract: This study examined the relation between religiousness and depressive symptoms in African American, Asian American, European American, Hispanic American, and Native American adolescents .N D 13,317/ in the United States with selfesteem and school attachment as potential mediators in this link. The data were taken from a nationally represented sample of adolescents in Grades 7 through 12, from the National Longitudinal Study of Adolescent Health (Add Health). Structural equation analyses with measurement and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 35 publications
2
40
1
Order By: Relevance
“…However, little attention has been paid to this link among children and adolescents [7,8]. In recent, nationally representative samples of adolescents, higher levels of religious beliefs and involvement were associated with lower levels of depressive symptoms [9,10]. Controlling for demographic variables (i.e., gender, race, grade level, and socioeconomic status), one study found that perceived social support from adolescents' religious community was associated with lower levels of depressive symptoms; conversely, perceived criticism and demands from their religious community were associated with higher levels of depressive symptoms [11].…”
mentioning
confidence: 99%
“…However, little attention has been paid to this link among children and adolescents [7,8]. In recent, nationally representative samples of adolescents, higher levels of religious beliefs and involvement were associated with lower levels of depressive symptoms [9,10]. Controlling for demographic variables (i.e., gender, race, grade level, and socioeconomic status), one study found that perceived social support from adolescents' religious community was associated with lower levels of depressive symptoms; conversely, perceived criticism and demands from their religious community were associated with higher levels of depressive symptoms [11].…”
mentioning
confidence: 99%
“…Implications of religious involvement for Asian American youths might be different from those for majority American youths due to the religious heterogeneity of Asian immigrants (Le et al, 2007) and the immigrant contexts that shape youth experiences. In general, evidence suggests that religion is important to Asian American youths.…”
Section: Asian American Adolescents' Religious Involvement and Ethnicmentioning
confidence: 99%
“…However, evidence also indicates variation among Asian American youths in regards to religiosity. For example, in a study (Le et al, 2007) that examined the relation between religiousness and adolescent outcomes using the National Longitudinal Study of Adolescent Health data, religiousness was shown to be a significant protective factor for depression among European American and African American adolescents but not among Asian Americans. The authors attributed this to the heterogeneity among Asian Americans' religiosity, suggesting the need for more nuanced analyses of subgroups within different ethnic groups.…”
Section: Asian American Adolescents' Religious Involvement and Ethnicmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, high religious orientation may serve as a form of social capital that enhances adolescent development. Indeed, researchers have reported that participation in religious activities and a belief in the importance of religion were associated with increased self-esteem (Le, Tov, & Taylor, 2007) and decreased aggression (Hollister-Wagner, Foshee, & Jackson, 2001;Leach, Berman, & Eubanks, 2008). Support from parents represents a positive proximal process in the family microsystem that also serves as an important source of social capital for youth.…”
Section: Social Capital Positive Proximal Processes and Mental Healmentioning
confidence: 99%